Pneumatic rotary nozzle structure optimization design and airflow characteristics analysis - Wang, Pengyu; Yang, Wenlong (Advances in mechanical engineering, 2023)
In this paper, the impact jet field between the pneumatic nozzle and the workpiece surface is simulated by the computational fluid dynamics method, and the influence law of the nozzle structure parameters on the jet performance is obtained by combining the response surface method (RSM), so as to improve the dust removal effect of the pneumatic nozzle. Firstly, the nozzle impact jet field calculation model was established, and the experimental platform of wind speed and volume measurement was built to verify the accuracy of the numerical calculation model and to simulate and analyze the jet field distribution characteristics of the nozzle under rotating working conditions. Then combined with the Box-Behnken Design (BBD) method, a response surface regression model with nozzle inlet radius (R1), cylindrical section length (L), and cone angle (A) as design variables and nozzle jet fixed point (20 mm) flow rate as the target variable was established to find the optimal combination of nozzle characteristics parameters. The results show that the optimized nozzle characteristics parameters using RSM can effectively improve the nozzle jet performance, the optimized jet flow rate increased by 8.38%, and can be more effective in dust removal; jet pressure on the workpiece surface decreases as the nozzle incidence angle increases; in the speed range of 400–1200 r/min, the pressure change caused by the jet on the wall surface is small, and the flow rate is relatively stable.